Ekonomi Hijau: Integrasi Bisnis, Teknologi, Pemasaran, Dan Sistem Sertifikasi Berkelanjutan - Elisabeth Tamara Ratu Hutauruk; Irna Della Br Ginting; Nataline Simanjuntak; Bonaraja Purba (Sharing: Journal of Islamic Economics Management and Business, 2026)
Green economy is a development concept that emphasizes the balance between economic growth, environmental sustainability, and natural resource conservation. This concept has become increasingly important in addressing global environmental challenges. This article aims to analyze the relationship between the green economy and key sectors such as business, technology, marketing, and green certification in supporting sustainable development. This study uses a literature review method with a qualitative descriptive approach based on various relevant scientific sources. The findings show that the implementation of a green economy encourages business transformation toward more environmentally friendly practices, supported by sustainable technological innovation. In addition, green marketing plays an important role in increasing consumer awareness of sustainable products, while green certification serves as a standard to ensure compliance with sustainability principles. Thus, the green economy has a strategic role in building an integrated and sustainable economic system.